Africa joins the growth capital revolution: Examining the growth of venture capital in the continent - Osborn, Tom (My University, 2019)
Small businesses play an important role in African economies. But because of a funding gap, many of these businesses struggle to access adequate growth capital. Venture capital (VC) can fill this funding gap and has emerged as an important global source of growth capital. While VC can help grow African businesses, our understanding of VC activities in Africa remains limited. Sparse research has limited the ability of small business owners to expand their financing options. We use a sample of 120 VC funds that primarily invest in Africa to investigate trends in the growth of VC activities in Africa, as well as to examine the associations between VC fundraising and micro-level firm variables between 2000-2018. We find that at least $4.57b of VC funding has been raised during this period by African VC funds. We observe that most funds keep diversified portfolios and invest in businesses at various stages of growth, and that funds prefer to keep their investment activities within domiciled countries. Using a multiple linear regression model, we find significant associations between VC fundraising and VC fund type, location focus, and vintage year. We do not find any associations between VC fundraising and industry focus, fund manager domicile or fundraising target size. These findings are important because small businesses can better assess their funding options, VC firms can update their strategies, and policy makers can update their policy priorities.
Keywords: africa; financial inclusion; growth capital; small business; vc; venture capital